Distribusi Suplemen Tablet Tambah Darah (TTD) Ibu Hamil Pada Era Pandemi Covid-19 Di Kabupaten Banyumas - Alfi Noviyana; Purwati (NERSMID : Jurnal Keperawatan dan Kebidanan, 2021)
Pregnant women are a vulnerable group, have a high risk of anemia. Anemia will reduce the body's resistance so that it is vulnerable to various infections, including COVID-19 infection. Prevention of nutritional anemia in pregnant women is carried out by giving a minimum of 90 Blood Add Tablets (TTD) during pregnancy and starting as early as possible with the technical provision of 10 items every month for examination visits for pregnant women. The COVID-19 pandemic has had an impact on the distribution of blood-added tablets to pregnant women. The purpose of the study was to find out how to distribute blood-added tablets, provide health education regarding the consumption of blood-added tablets and compliance with blood-added tablets consumption during the pandemic. This study uses a qualitative method with a case study approach. The study was located in the Puskesmas in the Banyumas district, with a total of 2 Puskesmas namely, Puskesmas Purwokerto Selatan and Puskesmas Kembaran I. This study used purposive sampling by taking 4 main informants consisting of 2 coordinating midwives and 2 nutrition managers, while the supporting informants consisted of of 2 pregnant women and 1 Kepala Bagian KIA of the Banyumas Health Office. ANC services and distribution of blood-added tablets during the COVID-19 pandemic will continue to be carried out with certain strategies in accordance with established policies by taking into account health protocols. The provision of health education and counseling is carried out online and compliance monitoring is still subjective and uses the KIA handbook.